The digital footprint of academics in Karnataka: A study of research engagement and performance on ResearchGate - Sulakshana, H V; Sampath Kumar, B. T. (Iberoamerican Journal of Science Measurement and Communication (Online), 2025)
Objective. This study explored the research engagement and performance of faculty members from selected universities in Karnataka, India, on ResearchGate (RG). The study assessed several metrics, including research contributions, forms of publications, and the availability of full-text documents. The objective was to identify the most productive universities, departments, and individual faculty members. Furthermore, the study undertook a multifaceted examination of the correlation between various RG metrics, with the objective of elucidating their interrelationship. Methodology. A representative sample of universities in Karnataka was selected based on academic reputation and diversity. Data were collected from the profiles of 330 faculty members who had created RG profiles, including details on publications read, profile views, citations, H-index, participation in the question and answers (Q&A) section, research interest (RI) score, followers, and following. Subsequent correlation analyses were conducted to assess the relationship among these metrics. Results. The study revealed that a mere 38.02% of faculty members across a selection of universities in Karnataka have established RG profiles. The University of Mysore demonstrated the highest level of research productivity, with 5,235 publications and 71,814 citations. Among the faculty members, K. R. Kini from the University of Mysore exhibited the highest RI score (7,712), followed by Gireesha B. J. from Kuvempu University, who attained an RI score of 5,261. The Department of Chemistry at Karnatak University demonstrated the highest level of productivity, with a total of 1,004 documents and an RI score of 8268.3. Statistical analyses revealed a significant positive correlation between university age and the number of RG profiles, as well as between the number of publications and citations. However, the correlation between the number of publications and the RI score was moderate and not statistically significant. Conclusion. This study underscored the growing role of academic social networking platforms in scholarly communication. By identifying key trends in research visibility and engagement, the study provided valuable insights for researchers seeking to optimize their RG presence. While the study identified correlations among various RG metrics, its reliance on publicly available profile data, which may be subject to updates and inconsistencies, was a limitation.